2018
DOI: 10.1101/365171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of permethrin resistance andkdralleles in Florida strains ofAedes aegypti(L.) andAedes albopictus(Skuse)

Abstract: Recent outbreaks of locally transmitted dengue and Zika viruses in Florida have placed more emphasis on the importance of integrated vector management plans for Aedes aegypti (L.) and Aedes albopictus Skuse. Adulticiding, primarily with pyrethroids, can be the best option available for the immediate control of potentially arbovirus-infected mosquitoes during outbreak situations. While pyrethroid resistance is common in Ae. aegypti worldwide and testing is recommended by CDC and WHO, resistance to this class of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…While other mechanisms related to the outcome of resistance in this and related species have been identified(16), variation in resistance status in the Ae. aegypti populations studied here is highly correlated with frequencies of these mutations, as was shown in Estep et al2018(18), where the authors found a Pearson correlation coefficient of 0.905 between frequencies of the IICC genotype and the permethrin resistance ratio (3).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…While other mechanisms related to the outcome of resistance in this and related species have been identified(16), variation in resistance status in the Ae. aegypti populations studied here is highly correlated with frequencies of these mutations, as was shown in Estep et al2018(18), where the authors found a Pearson correlation coefficient of 0.905 between frequencies of the IICC genotype and the permethrin resistance ratio (3).…”
supporting
confidence: 83%
“…The data used in this study were collected as part of a statewide insecticide resistance monitoring effort that is described in detail in Estep et al 2018 (18). The frequencies of kdr genotypes were determined for Ae.…”
Section: Methodsmentioning
confidence: 99%
“…The first mutation at codon 1016 results in a change from a valine (V) to an isoleucine (I) (17), while the second mutation at codon 1534 results in a change from a phenylalanine (F) to a cysteine (C). The frequency of individuals with the homozygous mutant variant at both sites (IICC) has a strong positive correlation with pyrethroid resistance in tested populations and can be used to estimate on-theground resistance (18,19). Mosquitoes that are heterozygous at both sites typically exhibit limited resistance to pyrethroids (20).…”
Section: Introductionmentioning
confidence: 99%
“…A case in point was the 2016 Zika outbreak in Miami‐Dade County that was in part due to insecticide resistance in Ae. aegypti populations (Estep et al 2018) and made it harder to control mosquitoes. New and alternative control strategies are needed to address this problem.…”
Section: Introductionmentioning
confidence: 99%